Kinds ofExtensiveReading Materials and their Influence on Learners’ Language Skills in Language Classrooms in Kenya - Wafula, Lorna; Barasa, Peter; Agalo, Joyce (Journal of Educational Policy and Entrepreneurial Research, 2017)
his study investigatedkinds of extensive reading materials and their influence on learners’ language skills in language classrooms in Kenya. It scrutinizedthe kinds of reading materials that learnersare exposed to in language classrooms and how they influence theirlanguage skills. The target population was the teachers and learners of English language in secondary schools in Uasin Gishu County, Kenya. Purposive sampling techniques were usedto select four secondary schools in Eldoret Municipality to participate inthe study by giving information through language tests, focus group discussions and interview schedules. All the form three students in the four sampled secondary schools participated in language tests. Twelvestudents were purposively chosen to participate in focus group discussionsand one teacher of English from each of thefour sampledschools participated in the interview schedule. Descriptivetechniqueswere used in the analysis of the data collected. It was concludedthatsecondary schools in Kenya, didnot have reading materials that motivatedlearners to read extensively.It wasrecommended that,the Ministry of Education should set up network systemsthat will assist learners’access plenty and variedreading materials.
Keywords: Extensive Reading; Reading Materials; Language skills; Language classrooms